Risk Management And Public Service: Integrated Analysis At The Public Sector Organization - Meinarni Asnawi; Rudiawie Larasati; Azhar Syahrir (Universitas Muhammadiyah Malang, 2023)
Purpose – This research aims to describe and analyze integrated Risk Management and Public Service at Public Sector Organizations Methodology/approach – The Study is a quantitative research approach that uses online-based data collection methods (e_ questionnaires) combined with interviews to get their views on integration risk management implementation and public service. The sample in this study was 94 respondents from three (3) public organizations, consisting of the Papua Provincial Government (Finance Staff & APIP), Higher Education Internal Audit (SPI), and Financial Supervisory Institution (BPKP & BPK). Findings – The results of the analysis show that there are a few key points on how risk management is important and has a close relationship with public service, like this protecting public interest, Enhancing Service Delivery, Allocating Resources Efficiently, Ensuring Compliance and Accountability, Emergency Preparedness and Response, Reputation Management, and Long-term Sustainability. The integration of risk management in public services shows a positive relationship and can contribute to service reliability, better financial management, minimizing fraud and increasing compliance with regulations, maximizing the utilization of assets owned by the government, and having a speed of response to emergency conditions or events, and being able to mitigate risks that may occur. Practical implications – Risk management in public service helps ensure efficient resource allocation, protect public interests, enhance service delivery, and maintain the integrity and reputation of public organizations. Public service agencies can better serve their communities and fulfill their mandate by proactively managing risks. Originality/value – This research combines behavioral and psychological approaches to test the occurrence of Risk Management in the Public Sector.